Grip Preference, Dermatoglyphics, and Hand Use in Captive Chimpanzees (Pan troglodytes) - Hopkins, William D. (2005)
This paper examined the association between grip type, hand use, and fingerprint patterns in a sample of captive chimpanzees. Grip type for simple reaching was assessed for the left and right hand and classified as thumb-index, middle-index, or single-digit responses. Fingerprint patterns were characterized as whorls, loops, or arches on each finger. The results indicated that chimpanzees exhibit significantly more thumb-index responses for the right compared to the left hand. In addition, thumb-index responses were more prevalent for subjects that had a whorl compared to a loop or arch on their thumb. The results suggest that fingerprint patterns are associated with individual differences in grasping type in chimpanzees as well as some variation in hand use.